Epilepsy with onset at over 50 years of age: clinical and electroencephalographic characteristics - Glória Maria Almeida Souza Tedrus; Lineu Corrêa Fonseca; Elizardo Nogueira Junior; Daniele Pazetto (Arquivos de Neuro-Psiquiatria)
Epilepsy in older individuals has an elevated incidence. The objective of the present work was to evaluate the clinical, EEG and brain imaging aspects in patients showing late-onset epilepsy. Fifty-five patients with late-onset epilepsy (older than 50 years) were evaluated. They were composed of two groups according to the onset age of the epilepsy seizure (ES): 51-60 (G51-60) and over 60 (G60+) years. Focal ES predominated although they were less frequent in G60+. The occurrence of status epilepticus was high and more frequent in G60+ whereas seizures in series predominated in G51-60. Symptomatic epilepsy was more frequent and the vascular etiology predominated. Epileptiform activity was associated with a greater number of ES, and background activity abnormalities were more frequent in G60+. In conclusion, epilepsy with onset at over 50 was predominantly focal and symptomatic, with a high occurrence of status epilepticus and of seizures in series.